Work-related stress according to the demand-control model and minor psychic disorders in nursing workers - Janete de Souza Urbanetto; Maria Cristina Cademartori Magalhaes; Vanessa Oreda Maciel; Viviane Massena SantAnna; Andreia da Silva Gustavo; Carlos Eduardo Poli-; Tania Solange Bosi de Souza Magnago (SciELO, 2013)
This was a cross-sectional study that aimed to assess the association between work-related stress according to the Demand-Control Model, and the occurrence of Minor Psychic Disorder (MPD) in nursing workers. The participants were 335 professionals, out of which 245 were nursing technicians, aged predominantly between 20 and 40 years. Data were collected using the Job Stress Scale and the Self-Reporting Questionnaire-20. The analysis was performed using descriptive and analytical statistics. The prevalence of suspected MPD was 20.6%. Workers classified in the quadrants active job and high strain of the Demand-Control Model presented higher potential for developing MPD compared with those classified in the quadrant low strain. In conclusion, stress affects the mental health of workers and the aspects related to high psychological demands and high control still require further insight in order to understand their influence on the disease processes of nursing workers.